2009
DOI: 10.1016/j.biopsycho.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological markers of pre-lexical speech processing: Evidence for bottom–up and top–down effects on spoken word processing

Abstract: Page 1 AbstractThe present study was designed to investigate the electrophysiological consequences of a mismatch between initial phoneme expectations and the actual spoken input. Participants were presented with a word/nonword prompt with the instruction to delete the initial sound (e.g., snap without the /s/; snoth without the /s/) and determine the resulting segment. Following the prompt, an aurally presented response that matched/mismatched expectations (e.g., nap/tap; noth/toth) was presented. The Phonolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 33 publications
9
54
1
1
Order By: Relevance
“…The timing of this effect, and its direction, are congruent with reports of an ERP effect known as the phonological mapping negativity (PMN: Newman & Conolly, 2009;Steinhauer & Connolly, 2008), understood to index goodness of fit of a phonological form to expectations generated by contexts including written words (e.g., Connolly, Service, D'Arcy, Kujala, & Alho, 2001) and also picture stimuli (e.g., Duta et al, 2012). The effect has been shown to be discrete from well known N400 effects of semantic congruence, and can be observed around 230-310 ms (Desroches, Newman, & Joanisse, 2008).…”
Section: Mid Time Window 280-320 Mssupporting
confidence: 74%
“…The timing of this effect, and its direction, are congruent with reports of an ERP effect known as the phonological mapping negativity (PMN: Newman & Conolly, 2009;Steinhauer & Connolly, 2008), understood to index goodness of fit of a phonological form to expectations generated by contexts including written words (e.g., Connolly, Service, D'Arcy, Kujala, & Alho, 2001) and also picture stimuli (e.g., Duta et al, 2012). The effect has been shown to be discrete from well known N400 effects of semantic congruence, and can be observed around 230-310 ms (Desroches, Newman, & Joanisse, 2008).…”
Section: Mid Time Window 280-320 Mssupporting
confidence: 74%
“…On the PMN time window, a main effect of site was found (F(3,75) = 61.46, p < .001) showing positive values at the anterior and frontocentral sites and negative values at the centroparietal and posterior sites. As effects on the PMN are usually centered on frontocentral recording sites (e.g., Newman & Connolly, 2009), neighborhood density and frequency effects were examined on these particular sites. While no effect of frequency was observed (F(1,25) = 0.16, p > .2), an effect of density was found (F(1,25) = 5.32, p < .05).…”
Section: Erp Resultsmentioning
confidence: 99%
“…In particular, a number of studies have shown that it is elicited when the perceived word and the expected one mismatch in the initial phonemes (Connolly & Phillips, 1994;Desroches et al, 2009;Hagoort & Brown, 2000;Newman et al, 2003;Newman & Connolly, 2009). Moreover, PMN was found during the processing of spoken word and nonwords (Newman & Connolly, 2009), but not during visual word processing (Connolly & Phillips, 1994). Hence, it has been proposed that PMN reflects prelexical processing, and in particular phonological mapping.…”
Section: Electrophysiological Correlates Of Spoken Word Recognitionmentioning
confidence: 99%
“…Several studies have confirmed that the PMN is a stand-alone reflection of pre-lexical phonological processing of speech that is independent of semantic top-down influences (Diaz & Swaab, 2007;Newman, Connolly, Service, & McIvor, 2003). Recent data suggests a functional dissociation between the PMN and N400, and authors assimilated the PMN as a neural marker representing the goodness-of-fit between initial phoneme expectations and the actual spoken input (Newman & Connolly, 2009). …”
Section: Discussionmentioning
confidence: 88%
“…This component recorded in response to words as well as pseudo-words was not modulated by the lexical factor, contrary to the N400, but appeared to be sensitive to phonological expectation rather than lexical expectation. It was found to be localized over parietal electrodes (Newman & Connolly, 2009).…”
Section: Introductionmentioning
confidence: 98%